2007
DOI: 10.1097/01.mlr.0000250482.07970.5f
|View full text |Cite
|
Sign up to set email alerts
|

Medical Specialists’ Patient-Centered Communication and Patient-Reported Outcomes

Abstract: Medical specialists' facilitating behavior was associated with greater satisfaction in patients who were less confident in communicating with their doctor. Patient-centered communication was not associated with patients' health status or adherence in general, but facilitating behavior was positively related to the adherence of patients with a foreign primary language. In general, patients appeared to be more satisfied after an encounter with a more-facilitating and a less-inhibiting physician, but these associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 40 publications
3
57
1
4
Order By: Relevance
“…Patient-provider communication and relationships were closely tied to overall perceptions of quality of care. This is corroborated by previous literature indicating that clear communication with providers and a sense of trust and respect is vital for patient satisfaction [14,[30][31][32]. Consistent with prior studies [3,5], we found that environments of care, both physical and social, and accessibility of care were also important aspects of the patient experience.…”
Section: Discussionsupporting
confidence: 92%
“…Patient-provider communication and relationships were closely tied to overall perceptions of quality of care. This is corroborated by previous literature indicating that clear communication with providers and a sense of trust and respect is vital for patient satisfaction [14,[30][31][32]. Consistent with prior studies [3,5], we found that environments of care, both physical and social, and accessibility of care were also important aspects of the patient experience.…”
Section: Discussionsupporting
confidence: 92%
“…Results support previous findings that indicate there is no single preferred approach with regards to the process and content of prognosis communication for cardiologists and patients with advanced HF [36]. The contextual preferences described here are highly influential for cardiologists and patients as they choose to engage (or not) in HF-related prognosis communication and they must be considered by those who encourage the implementation of any prognostic communication formula [30].…”
Section: Preferences Are Contextualsupporting
confidence: 74%
“…Regarding the direct influences of the doctor-patient relationship on the health status contradicting evidence was presented: While Cooper et al (2011) reported more positive communication, and Zandbelt et al (2007) observed improved doctor-patient relationships to be associated with higher patient activation, both studies found no direct influence on the health status. In contrast Auerbach et al (2002) realized a better doctor-patient relationship to be associated with improved diseaserelated behavior and a better health status, and Wodskou et al (2014) reported that the physicians' empathy correlated with a better health status of their patients.…”
Section: Relationship Buildingmentioning
confidence: 77%